Mice lacking the syndecan-3 gene are resistant to diet-induced obesity - April D. Strader; Ofer Reizes; Stephen C. Woods; Stephen C. Benoit; Randy J. Seeley (2004)
The accurate matching of caloric intake to caloric expenditure involves a complex system of peripheral signals and numerous CNS neurotransmitter systems. Syndecans are a family of membrane-bound heparan sulfate proteoglycans that modulate ligand-receptor interactions. Syndecan-3 is heavily expressed in several areas of the brain, including hypothalamic nuclei, which are known to regulate energy balance. In particular, syndecans have been implicated in modulation of the activity of the melanocortin system, which potently regulates energy intake, energy expenditure, and peripheral glucose metabolism. Our data demonstrate that syndecan-3–null mice have reduced adipose content compared with wild-type mice. On a high-fat diet, syndecan-3–null male and female mice exhibited a partial resistance to obesity due to reduced food intake in males and increased energy expenditure in females relative to that of wild-type mice. As a result, syndecan-3–null mice on a high-fat diet accumulated less adipose mass and showed improved glucose tolerance compared with wild-type controls. The data implicate syndecan-3 in the regulation of body weight and suggest that inhibition of syndecan-3 may provide a therapeutic approach for the treatment of obesity resulting from exposure to high-fat diets.